Supplementation of Lactobacillus acidophilus in compound diets for Labeo rohita fingerlings - Ghosh, K; Sen, S K; Ray, A K (Indian Journal of Fisheries, 2011)
Supplementation of Lactobacillus acidophilus in compound diets for Labeo rohita fingerlings